(untitled) (British Journal of Global Ecology and Sustainable Development, 2026)
This article teaches that errors are not only an obstacle to learning, but also a way of developing the student and creative thinking. It describes the causes, factors, analysis of errors, ways to eliminate errors, principles, strategies, importance and practical recommendations.